At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To solve the equation \(\sqrt{2n + 28} - 4\sqrt{n} = 0\), we'll proceed step-by-step:
1. Isolate one of the square root terms:
First, let's isolate \(\sqrt{2n + 28}\) on one side of the equation:
[tex]\[ \sqrt{2n + 28} = 4 \sqrt{n} \][/tex]
2. Square both sides:
To eliminate the square roots, we'll square both sides of the equation:
[tex]\[ (\sqrt{2n + 28})^2 = (4 \sqrt{n})^2 \][/tex]
Simplify the equation:
[tex]\[ 2n + 28 = 16n \][/tex]
3. Solve for \(n\):
Rearrange the equation to isolate \(n\):
[tex]\[ 2n + 28 = 16n \][/tex]
Subtract \(2n\) from both sides:
[tex]\[ 28 = 14n \][/tex]
Divide both sides by 14:
[tex]\[ n = 2 \][/tex]
4. Check the solution:
We should verify if \(n = 2\) satisfies the original equation. Substitute \(n = 2\) back into the original equation:
[tex]\[ \sqrt{2(2) + 28} - 4 \sqrt{2} = \sqrt{4 + 28} - 4 \sqrt{2} = \sqrt{32} - 4 \sqrt{2} \][/tex]
Since \(\sqrt{32} = 4 \sqrt{2}\), we get:
[tex]\[ 4 \sqrt{2} - 4 \sqrt{2} = 0 \][/tex]
The left side equals the right side, so \(n = 2\) is indeed a solution.
Thus, the solution to the equation \(\sqrt{2n + 28} - 4\sqrt{n} = 0\) is \(n = 2\).
Among the given options:
- \(n = 2\)
- \(n = 4\)
- \(n = 7\)
- \(n = 14\)
The correct answer is [tex]\(n = 2\)[/tex].
1. Isolate one of the square root terms:
First, let's isolate \(\sqrt{2n + 28}\) on one side of the equation:
[tex]\[ \sqrt{2n + 28} = 4 \sqrt{n} \][/tex]
2. Square both sides:
To eliminate the square roots, we'll square both sides of the equation:
[tex]\[ (\sqrt{2n + 28})^2 = (4 \sqrt{n})^2 \][/tex]
Simplify the equation:
[tex]\[ 2n + 28 = 16n \][/tex]
3. Solve for \(n\):
Rearrange the equation to isolate \(n\):
[tex]\[ 2n + 28 = 16n \][/tex]
Subtract \(2n\) from both sides:
[tex]\[ 28 = 14n \][/tex]
Divide both sides by 14:
[tex]\[ n = 2 \][/tex]
4. Check the solution:
We should verify if \(n = 2\) satisfies the original equation. Substitute \(n = 2\) back into the original equation:
[tex]\[ \sqrt{2(2) + 28} - 4 \sqrt{2} = \sqrt{4 + 28} - 4 \sqrt{2} = \sqrt{32} - 4 \sqrt{2} \][/tex]
Since \(\sqrt{32} = 4 \sqrt{2}\), we get:
[tex]\[ 4 \sqrt{2} - 4 \sqrt{2} = 0 \][/tex]
The left side equals the right side, so \(n = 2\) is indeed a solution.
Thus, the solution to the equation \(\sqrt{2n + 28} - 4\sqrt{n} = 0\) is \(n = 2\).
Among the given options:
- \(n = 2\)
- \(n = 4\)
- \(n = 7\)
- \(n = 14\)
The correct answer is [tex]\(n = 2\)[/tex].
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.